Efektivitas Sistem Informasi Administrasi Kependudukan (Siak) Terpusat Pada Dinas Kependudukan Dan Pencatatan Sipil Lombok Timur - Nova Hari Santhi; junaidi junaidi (Universitas 45 Surabaya, 2024)
According to Law Number 23 of 2006 which was later revised into Law Number 24 of 2013 concerning Population Administration, the definition of a population administration information system (SIAK) is an information system that utilizes information and communication technology to facilitate the management of population administration information at the Operator level. /Executing Agency as one unit. This research aims to; To find out and describe the effectiveness of the population administration information system centered on the East Lombok Population and Civil Registration Service, this type of research is descriptive qualitative. The informants in this research were 7 people, key informants, main informants and additional informants were 5 people. The data collection techniques used were interviews, observation and documentation. The data analysis method uses descriptive analysis. The results of this research are that the effectiveness of SIAK has been optimally implemented in the East Lombok Regency Population and Civil Registration Service, this can be seen from the ease with which employees can carry out their work, such as when making community population administration, they now don't have to wait a long time for completion. You can now wait for the creation of the Adminduk and it will be ready immediately. The existence of SIAK also speeds up services for the community.